Evaluation of intraoperative subcutaneous anesthetic infiltration for pain management in patients undergoing total thyroidectomy - Phamella Carlesse; Nathalia Cardoso; Tamara Harati; Bruna Lapichini; Daniel Herman Partezani; Leandro Luongo de Matos; Rogério Aparecido Dedivitis (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To evaluate the efficacy of intraoperative Bupivacaine application in reducing postoperative pain among patients undergoing total thyroidectomy. Methods: A prospective study was carried out with 153 female patients undergoing total thyroidectomy, with a randomization protocol for topical anesthetic infiltration. Postoperative pain intensity was self-reported by the patients using the Visual Analog Scale (VAS) at the 1st, 6th, and 24th postoperative hours. Results: Comparative analysis revealed that patients who did not receive anesthetic infiltration experienced, on average, higher pain levels during all three observation periods (1st and 6th hours, and 24th hour; p = 0.0001 – repeated measures ANOVA multiple test) relative to those who received the anesthetic. Isolated observations showed that pain was significantly less severe at the 24th hour compared to the 6th hour (p = 0.001 – repeated measures ANOVA test). Conclusion: Topical anesthetic infiltration proves to be an effective tool for managing post-thyroidectomy pain. Level of evidence: Level III.